Sport and Oxidative Stress in Oncological Patients - Knop, K.; Schwan, R.; Bongartz, M.; Bloch, W.; Brixius, K.; Baumann, F. (International Journal of Sports Medicine, 2011)
Oxidative stress is thought to be an important factor in the onset, progression and recurrence of cancer. In order to investigate how it is influenced by physical activity, we measured oxidative stress and antioxidative capacity (aoC) in 12 women with breast cancer and 6 men with prostate cancer, before and after long hiking trips. Before the hike, the men had a ROS-concentration of 1.8±0.6 mM H2O2 and an aoC of 0.7±0.6 mM Trolox-equivalent (Tro), while the women had a ROS-concentration of 3.1±0.7 mM H2O2 and an aoC of 1.2±0.2 mM Tro. After the hike, women showed no significant change in ROS and a significant increase in aoC (1.3±0.2 mM Tro), while the ROS concentration in men increased significantly (2.1±0.3 mM H2O2) and their aoC decreased (0.25±0.1 mM Tro). After a regenerative phase, the ROS concentration of the men decreased to 1.7±0.4 mM H2O2 and their aoC recovered significantly (1.2±0.4 mM Tro), while the women presented no significant change in the concentration of H2O2 but showed an ulterior increase in antioxidant capacity (2.05±0.43 mM Tro). From this data we conclude that physical training programs as for example long distance hiking trips can improve the aoC in the blood of oncological patients.
Keywords: oxidative stress; antioxidant capacity; cancer; sport